SIFAT FISIK MATERIAL PAPAN KOMPOSITE BERBAHAN SERAT TEBU DENGAN MATRIX RESIN POLYESTER - Dera, Nurmala Santi; Kilo, Faisal; Talango, Novriyanti; Ishak, Sahional; Lestari, Wahyu Dwi (Universitas Wahid Hasyim, 2023)
Sugar cane fiber is an organic waste mostly produced by sugar factories in Indonesia such as in Gorontalo Province. If it is properly processed, it will have high economic value and will help the community’s economy during Covid 19 pandemic. This fiber, however, is easy to find, and it is not dangerous for human health. The important thing is that this fiber can be degraded naturally. Hence it can be used as composite reinforcing fiber which can help overcome environment problems. This study aimed at investigating the physical characteristics of natural fiber composite-based new material with characteristics and structures which can be used for automotive industry. The method applied in this study was by doing physical test such as density, water content, water absorption level, and thickness development with random-pattern treatments consisting of fraction variations of sugar cane fiber volumes of 10%, 30%, and 50% and fraction variations of resin volumes of 90%, 80%, and 70%. Each treatment consisted of 3 specimens with determined size, and they were tested in laboratory in order to find out the physical. Findings revealed that the highest density was in specimen 3 with fiber volume of 50% and resin volume of 70%, and the average value was 1.162 g/cm3. Meanwhile, the highest water content was specimen 1 with fiber volume of 10% and resin volume of 90% obtaining value of 0.51%. The water absorption level during 24 hours that obtained maximal result and value of 6.89% was specimen 2 with fiber volume of 30% and resin volume of 80%. The result for thickness development during 24 hours that obtained value of 10% was specimen 1 with fiber volume of 10% and resin volume of 90%. If it is validated with Indonesian National Standard, some of physical test results should be further formulated to get result based on Indonesian National Standard. Regarding the explanation, the fiber volume and resin volume fractions highly influenced the natural fiber (sugar cane fiber) composite-based new material making and it can be used for automotive industry.